Coiled‐coil dimerization of the LOV2 domain of the blue‐light photoreceptor phototropin 1 from Arabidopsis thaliana. Issue 12 (1st December 2013) - Halavaty, Andrei S.; Moffat, Keith
<x xml:space="preserve">Abstract</x> A key role in signal transduction and dimerization mediated by Per–Arnt–Sim (PAS) domains is played by α‐helical linkers that flank the structurally similar α/β cores of these domains. However, crystal‐packing forces and the different construct lengths and sequences of the PAS domains influence the final length and orientation of the linkers relative to the core and create uncertainty in the exact mechanism of the linker function. Thus, structural characterization and comparison of the linkers within isolated PAS‐domain constructs and/or full‐length PAS‐containing proteins is important for clarification of the mechanism. The plant blue‐light photoreceptors phototropins possess two N‐terminal flavin mononucleotide‐based light, oxygen or voltage (LOV) domains (LOV1 and LOV2) that comprise a subclass of the PAS family and one C‐terminal serine/threonine kinase domain whose enzymatic activity is regulated by blue light. The dark‐adapted state crystal structures of the Arabidopsis thaliana phototropin 1 and phototropin 2 LOV1‐domain constructs flanked by an N‐terminal A′α helix and the structure of the phototropin 2 core LOV2 domain are known. Here, the crystal structure of the A. thaliana phototropin 1 LOV2 domain has been determined in its dark‐adapted state. The core is flanked by an N‐terminal A′α helix and a C‐terminal Jα helix similar to those in the previously reported structure of Avena sativa phototropin 1 LOV2. In contrast to the monomeric A. sativa LOV2, A. thaliana LOV2 is a dimer in which two A′α helices adopt a scissor‐like orientation at the dimer interface and form a short α‐helical coiled coil. The Jα helix predominantly interacts with the β‐sheet and plays a role in coiled‐coil formation and dimerization.